I'm telling the truth a first look at honesty - Thomas , Pat; Harker, Lesley (London Wayland, 2023)
In simple and reassuring terms, this entertaining book explores for young children aged approximately 4 - 8 what it means to be honest, why it is important, and what the consequences might be for those who are dishonest. Children are shown that although being honest can be hard sometimes, it is worth it. Everyone likes people who speak the truth and keep their word. Kids learn that when we all practise being honest, the world becomes a fairer and happier place to live in
Education
Keywords: Honesty; Picture books